Be a politician - Tucker, Walter Percival (My University, 1892)
Introduction: An election was recently held in one of our large cities. Voters, as usual, were scattered about discussing the candidates and the general situation. Presently one of them was approached by a very pleasant looking man, who leisurely sauntered up to our voter, shook hands, chatted a few moments, and gave him a cigar, which was of course put to use. Then after some more chatting he produced a ticket having on it the names of some special friends—good, straight forward men—for whom he’d like the voter to cast his ballot; indeed, he would give him a dollar to do so. And to complete the little episode, the voter presently dropped the ticket into the ballot box and the dollar into his pocket. Then our genteel friend wandered on to fresh pastures. That man was a politician, as we generally consider the term; but not the politician I have in mind. The one to whom I would ask your indulgence is not he whose livelihood depends upon his success at bribery among the voters; but he is the voter himself—the voter not led by unprincipled demagogues who would keep him in ignorance of the good qualities of an opposing platform or candidate and fire him with passion against the other party; but the voter who investigates for himself, thinks for himself, and acts for himself—the voter who reads both parties’ papers, hears both parties’ speakers, and studies the question under dispute from the lefty standpoint of a truth-seeker—not that of an office-seeker--, and the voter who then applies the knowledge thus acquired with the laudable intention of benefitting as much as possible the public.
Citation: Tucker, Walter Percival. Be a politician. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Politician; Election; Ballot; Voting; Bribery; Political Science; Theses; Manuscripts (documents)